Optometry Sales and Inventory Management System - Shah Rizal, Iman Insyirah; Marjudi, Suziyanti (Applied Information Technology And Computer Science, 2026)
The specialized needs of optical stores and optometry clinics create unique challenges when it comes to managing sales and inventory. These include the handling of prescriptions, tracking frame and lens inventories, and maintaining seamless customer interactions. In the case study of Specku Optometry store, reliance on a mix of manual processes and tools like Microsoft Excel has resulted in inaccuracies and inefficiencies. To address these issues and improve overall efficiency in daily operations, the Optometry Sales and Inventory Management System, a web-based software, has been developed. The primary objective of this software is to streamline daily tasks by managing and storing customer and product details, overseeing inventory levels, recording sales transactions, and generating reports that can provide valuable insights for business decision-making. In order to develop the software, the Agile model is chosen as the software development methodology due to its iterative approach, flexibility, and ability to adapt to user feedback throughout the development process. The software is also built using programming languages such as Hypertext Preprocessor (PHP), Hypertext Markup Language (HTML), Cascading Style Sheets (CSS), and JavaScript, with MySQL employed as the database. The developed system has resulted in improved inventory accuracy, reduced manual effort, and enhanced customer data management, providing valuable insights into sales trends for better decision-making. Finally, further research could be focused to explore the integration of advanced features like payment gateway, predictive analytics and barcode or QR scanning to further improve the system functionality.